The Protein Protocols Handbook - Walker, John M. (Humana Press, 2002)
From Reviews of the First Edition "...a must for researchers in protein chemistry and especially those with less experience..." -Doody's Health Sciences Book Review Journal "...definitely an indispensable benchtop handbook...highly recommended for all levels of research within the field."-Bioseparation "...a very useful tool for daily work." -Nahrung-Food Since publication of the bestselling first edition of John Walker's widely acclaimed Protein Protocols Handbook in 1996, there have been many highly significant developments in protein biochemistry. This greatly enhanced second edition introduces 60 critically important new chapters dealing with topics and techniques that have emerged since the first edition, as well as significantly updating the remaining articles. The new chapters cover many rapidly developing areas, particularly the application of mass spectrometry in protein characterization, as well as the now well-established 2-D PAGE technique in proteomics.